2000
DOI: 10.1889/1.1828767
|View full text |Cite
|
Sign up to set email alerts
|

Development of “Advanced TFT‐LCD” with good legibility under any ambient light intensity

Abstract: A new LCD referred to as an "Advanced TFT-LCD" has been developed. It consists of both transmissive and reflective electrodes in every pixel. Its subjective legibility and characteristics, such as contrast ratio, color gamut, and luminance, have been investigated at several ambient illumination intensities. As a result, it was confirmed that Advanced TFT-LCDs offer better legibility than transmissive LCDs under any ambient illumination intensity. FIGURE 1 -Panel structure of the Advanced TFT-LCD.FIGURE 2 -Cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 2 publications
1
21
0
Order By: Relevance
“…Kubo et al (2000) indicated that the TFT-LCD has been developed to excellent quality levels. Many researches indicated that the TFT-LCD has better visual performance than cathode ray tube (CRT) (Menozzi et al, 2000;Nose et al, 2000;Shieh and Lin, 2000;Wright et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Kubo et al (2000) indicated that the TFT-LCD has been developed to excellent quality levels. Many researches indicated that the TFT-LCD has better visual performance than cathode ray tube (CRT) (Menozzi et al, 2000;Nose et al, 2000;Shieh and Lin, 2000;Wright et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ambient illumination is an important consideration in workplace design with video display terminals. Although the surface of a TFT-LCD screen has an antiglare polarizer (Choi & Miyasaka, 1993), it still reflects the ambient lighting (Kubo, Uchi, Narutaki, Shinomiya, & Ishii, 2000). Pawlak (1986) proposed that the reflection property of a screen could be expressed as a reflection factor (q).…”
mentioning
confidence: 99%
“…Oyster (1999) reported that blink efficiency was dependent upon many factors: emotional state, mental effort, illumination level and atmospheric condition, etc. Kubo et al (2000) opined that the increase in the level of illumination resulted in more visual fatigue to the subject. Lin and Huang (2006) showed that there was no effect of ambient illumination on the character identification task for different contrast ratios.…”
Section: Methodsmentioning
confidence: 99%